Comparative Effect of Green and Blue Filters on Near Point of Accommodation among Emmetropes and Myopes: Green and Blue Filters: Accommodation among Emmetropes and Myopes - Saleem, Sundas; Ehsan, Rabia Bushra; Nadeem, Maryam Muhammad; Abdullah, Muhammad; Sanaullah, Tuba; Ishaq, Eesha (Pakistan Journal of Health Sciences, 2026)
Coloured filters are optical devices that selectively transmit certain wavelengths of light while absorbing others. Green and blue filters can reduce glare and improve contrast. Objectives: To determine the effect of green and blue filters on relieving excessive near point of accommodation among emmetropes and myopes. Methods: This analytical cross-sectional study was conducted at the Rashid Latif Khan University, Lahore, Pakistan, from May 2023 to January 2024. 110 participants of both genders, aged 15-30 years, were included. The participants were divided into emmetropes and myopes, with 55 participants in each group. The near point of accommodation (NPA) was assessed objectively using the RAF rule. Both groups were examined initially without any filter and then using green and blue filters. Data were analysed using SPSS-24. A repeated-measures ANOVA test was applied to compare the effect of green and blue filters in emmetropes and myopes. Results: Mean NPA ± SD without filter, with green filter, and with blue filter in emmetropes was 14.89 ± 1.64, 12.07 ± 1.15, and 12.25 ± 1.03, respectively, with (p<0.001) while, mean NPA ± SD without filter, with a green filter, and with a blue filter in myopes was 13.92 ± 1.68, 11.92 ± 0.58, and 12.53 ± 0.55, respectively, with (p<0.001) suggesting that both green and blue filters contribute to a reduction in excessive accommodation among emmetropes and myopes. Conclusions: The use of green and blue filters could decrease excessive NPA both in emmetropes and myopes (mild to moderate myopes).